Time Budget Pressure, Professional Ethics, Experience, Auditor Competence and Audit Quality: (Analysis at the Public Accounting Firm Drs Paul Hadiwinata, Hidajat, Arsono, Retno, Palilingan and Partners) - Faisal, Muhammad; Afra, Shafira Cahyaning (EQUITY, 2024)
This study seeks to analyse the impact of time budget pressure, the professional ethics of public accountants, work experience, and auditor competency on audit quality at PKF Public Accounting Firm, which is ranked among the top 10 accounting and professional services businesses in Indonesia. The study's population comprised 103 personnel from the Public Accounting Firm Drs Paul Hadiwinata, Hidajat, Arsono, Retno, Palilingan & Rekan (PKF International), including 93 Auditors and 10 HR Administrators and Staff. This study employed a purposive sampling methodology. This research employed a questionnaire as a survey instrument to gather respondent data. This study processed data from 68 respondents, representing 85 percent of the disseminated questionnaires. The software employed to examine the variable association in this study is SPSS 22. This study's findings demonstrate that time budget pressure, professional ethics, and experience positively influence audit quality. Conversely, auditor expertise does not influence audit quality.   Keywords: Time Budget Pressure, Professional Ethics of Public Accountants, Work Experience, Auditor Competence and Audit Quality.